The Analysis of The Metaphor in Selective Song Lyrics - Maulana, Nadya Najah (Educalitra: English Education, Linguistics, and Literature Journal, 2025)
This research analyzes metaphors in Bruno Mars' song lyrics, namely Talking to the Moon, It Will Rain, and Just the Way You Are. This study uses a qualitative approach with the theory of Lakoff & Johnson (2003) which divides metaphors into three types: ontological, structural, and orientational metaphors. The results of the analysis show that the metaphors in the songs describe feelings of love, sadness, and deep emotional connection. This research provides insight into the use of metaphor as a tool to convey complex emotions and meanings in song lyrics. Overall, 23 metaphors were found with a distribution of: 35% ontological metaphors, 35% structural metaphors, and 30% orientational metaphors.